THE IMPLEMENTATION OF INCLUSIVE EDUCATION POLICY IN INDONESIA: A LITERATURE REVIEW - Narendra Jumadil Haikal Ramadhan; Suti'ah; Abdul Aziz (Universitas PGRI Palembang, 2024)
This study seeks to gain a thorough understanding of the essential elements of inclusive education policy in Indonesia, as well as the obstacles faced in putting inclusive education into practice. This study used the Systematic Literature Review (SLR) method to collect and analyze data from 25 relevant articles on the topic under study and then selected 5 articles per topic. The findings show that there are several key components to ensuring equitable access to education for all children, including those with disabilities or special needs. However, the implementation of this policy is faced with various challenges, such as limited community involvement, lack of infrastructure and experts, inadequate teacher competence, limited teaching time, and policy misunderstandings and inconsistencies.